Cononsolvency of mono- and di-alkyl N-substituted poly(acrylamide)s and poly(vinyl caprolactam). (7th April 2015) - Scherzinger, C.; Balaceanu, A.; Hofmann, C.H.; Schwarz, A.; Leonhard, K.; Pich, A.; Richtering, W.
Abstract: In this comparative study we investigate the influence of the side chain substitution pattern on the volume phase transition temperature (VPTT) of thermo-sensitive polymer microgels. We especially focus on cononsolvency of water and methanol. We compare literature data for poly( N -isopropylacrylamide) (PNIPAM) that shows cononsolvency to experimental data for secondary amide poly( N -n-propylacrylamide) (PNNPAM) as well as tertiary poly( N, N -diethylacrylamide) (PDEAAM) and poly( N -vinyl-caprolactam) (PVCL). As methods we apply size determination by dynamic light scattering (DLS) as well as differential scanning calorimetry(DSC) and theoretical calculations using COSMO-RS (conductor-like screening model for real solvents). Clear differences are found for PDEAAM and PVCL in comparison to PNIPAM and PNNPAM. We ascribe the significant differences between PNIPAM and PNNPAM on the one hand and PDEAAM and PVCL on the other hand to the amide proton, which is present in PNIPAM and PNNPAM but not in the other two polymers. Graphical abstract: Highlights: Polymers from secondary and tertiary amides are compared. Thermoresponsive polyacrylamides with amide proton show cononsolvency. Thermoresponsive polyacrylamides without amide proton do not show cononsolvency. Tertiary poly( N -vinylcaprolactam) behaves like tertiary polyacrylamides. Calculations reproduce the experimental results.